(untitled) (Triyuga Academic Journal, 2024)
In Nepal, women’s involvement in politics has historically been constrained by entrenched traditional gender roles. Despite these limitations, several remarkable women have managed to rise above these constraints and become influential leaders within their communities. These instances highlight that simply implementing laws is not enough to ensure women’s participation; continuous monitoring is necessary to ensure the effective enforcement of these laws. This study employed a mixed research design, incorporating both liberal and representative political science theories, alongside a descriptive and analytical approach, which proved to be particularly effective under pragmatist philosophy. In 2017 local elections, women represented 40.95 percent of the elected officials. By 2022, this figure had seen a slight increase, with women comprising 41.21 percent of all elected representatives. This progress suggests that the 2022 elections offered a valuable opportunity to enhance women’s representation in politics, building on the significant achievements of 2017. This progress not only benefits political parties but also supports social justice. Many women, particularly those who have served in local government over the past four years, are eager to advance their political careers. Increasing female representation in public life is an important step toward achieving gender equality. Despite the Election Commission’s efforts to address concerns about women’s electoral participation, their actions have been insufficient, and political parties have exploited existing loopholes.